Private equity operational due diligence tools to evaluate liquidity, valuation, and documentation - Scharfman, Jason A., 1978- (Wiley finance series., 2012)
"A step-by-step guide to develop a flexible comprehensive operational due diligence program for private equity and real estate funds. Addressing the unique aspects and challenges associated with performing operational due diligence review of both private equity and real estate asset classes, this essential guide provides readers with the tools to develop a flexible comprehensive operational due diligence program for private equity and real estate. It includes techniques for analyzing fund legal documents and financial statements, as well as methods for evaluating operational risks concerning valuation methodologies, pricing documentation and illiquidity concerns. Covers topics including fund legal documents and financial statement analysis techniques Includes case studies in operational fraud. Companion website includes sample checklists, templates, spreadsheets, and links to laws and regulations referenced in the book. Equips investors with the tools to evaluate liquidity, valuation, and documentation. Also by Jason Scharfman: Hedge Fund Operational Due Diligence: Understanding the Risks. Filled with case studies, this book is required reading for private equity and real estate investors, as well as fund managers and service providers, for performing due diligence on the noninvestment risks associated with private equity and real estate funds"--